Eleven-layer co-extruded film containing PE-PA-EVOH material, preparation method and application in container liquid bag
By using eleven-layer co-extruded films containing PE-PA-EVOH in disposable container liquid bags, the problem of insufficient strength of the liquid bag is solved, and the high strength and puncture resistance is improved, satisfying the transportation of railway freight safety standards.
Patent Information
- Application Number
- CN202411574806.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing disposable container liquid bags have low strength and are prone to leakage due to violent shaking or scratching of foreign objects during transportation, making it difficult to meet the requirements of safe transportation.
Using eleven-layer coextruded films containing PE-PA-EVOH as the inner layer material of the liquid bag, the functional modification of graphene grafted nylon resin and ethylene-vinyl alcohol copolymer resin was prepared with extremely high strength and hardness. Membrane products meet the technical requirements for the containerized transportation of railway freight.
The tensile strength, elongation of break and puncture resistance of the liquid bag are improved, and the requirements of the TB/T2689.4-2018 standard are met, which significantly improves the mechanical properties and puncture resistance of the liquid bag, reducing leakage risks.
Smart Images

Figure CN119078332B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inner layer materials of disposable multi-layer container liquid bags, and specifically to an eleven-layer co-extruded film containing PE-PA-EVOH material, a preparation method and application in container liquid bags. Background Art
[0002] Container liquid bag is a new type of transport container that integrates storage and packaging functions and is suitable for bulk non-hazardous liquids or chemicals. The capacity of each liquid bag is 16-24m 3 , can store and transport up to 24,000 liters of liquid, lay it in a 20-inch standard container, fill it with liquid, tighten the filling port and close the door, then it can be distributed and shipped using a standard and flexible container logistics model.
[0003] The main material of container liquid bags is usually nylon or high-strength polyester, nitrile rubber polyester fiber cloth, and the double-sided coating uses materials such as polyimide, polyethylene, polypropylene, polyurethane and polyvinyl chloride mixture. In order to reduce the production and cleaning costs of liquid bags, disposable liquid bag products have been developed. This disposable liquid bag is divided into single-layer and multi-layer. Most single-layer liquid bags are made of polyethylene materials. The inner layer of the multi-layer liquid bag generally uses 4 layers of polyethylene materials with a thickness of 0.125mm, and the outer layer is polypropylene woven cloth. This disposable container liquid bag made of polyethylene and polypropylene has a lower cost, but the strength is reduced. If it is violently shaken during transportation or scratched by foreign objects, there will be a risk of leakage. Summary of the invention
[0004] The invention provides a method for preparing an eleven-layer co-extruded film containing a PE-PA-EVOH material. The film product prepared thereby can be used as an inner layer material of a disposable multi-layer container liquid bag.
[0005] An eleven-layer co-extruded film containing PE-PA-EVOH material, the product structure is:
[0006] LLDPE layer 1a, the formula of this layer is 100wt% linear low-density polyethylene resin LLDPE, and the amount of this layer is 10-20 parts by weight;
[0007] The first UHMWPE layer 2a, the formula of this layer is 100wt% ultra-high molecular weight polyethylene resin UHMWPE, and the amount of this layer is 5-15 parts by weight;
[0008] The first PE-g-MAH layer 3a, the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, and the amount of this layer is 1-5 parts by weight;
[0009] The first PA-gC(n) layer 4a, the formula of this layer is 100wt% graphene grafted nylon resin PA-gC(n), and the amount of this layer is 10-20 parts by weight;
[0010] The third PE-g-MAH layer 5a, the formula and dosage of this layer are the same as those of the first PE-g-MAH layer 3a;
[0011] EVOH layer 6, the formula of this layer is 100wt% ethylene-vinyl alcohol copolymer resin EVOH, and the amount of this layer is 5-15 parts by weight;
[0012] The fourth PE-g-MAH layer 5b, the formula and dosage of this layer are the same as those of the first PE-g-MAH layer 3a;
[0013] A second PA-gC(n) layer 4b, the formulation and dosage of which are the same as those of the first PA-gC(n) layer 4a;
[0014] The second PE-g-MAH layer 3b, the formulation and dosage of this layer are the same as those of the first PE-g-MAH layer 3a;
[0015] The second UHMWPE layer 2b, the formula and dosage of this layer are the same as the formula and dosage of the first UHMWPE layer 2a
[0016] LLDPE / EVA layer 1b, the formula of this layer is 60-90wt% linear low-density polyethylene resin LLDPE and 10-40wt% ethylene-vinyl acetate copolymer EVA, and the amount of this layer is 10-20 parts by weight;
[0017] The preparation method of graphene grafted nylon resin PA-gC(n) is as follows:
[0018] The epoxy coupling agent containing puncture-resistant flexible silicon oxygen chain alone or the epoxy coupling agent containing puncture-resistant flexible silicon oxygen chain and the cross-linking agent containing phenyl on the puncture-resistant flexible silicon oxygen chain are used to functionally modify the hydroxylated graphene nanosheets to obtain epoxy graphene nanosheets grafted with puncture-resistant flexible silicon oxygen chain;
[0019] The graphene grafted nylon resin PA-gC(n) is prepared by a ring-opening reaction between the terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin and the epoxy functional group of the epoxidized graphene nanosheet grafted with a puncture-resistant flexible silicon oxygen chain.
[0020] Preferably, the preparation method of the epoxy coupling agent containing the puncture-resistant flexible silicone chain is:
[0021] The alkenyl functional group of 1,7-divinyl-octamethyltetrasiloxane and the Si-H functional group of dimethylethoxysilane undergo an addition reaction, and the molar ratio of 1,7-divinyl-octamethyltetrasiloxane and dimethylethoxysilane participating in the reaction is controlled to be (1.01-1.05):1, thereby generating an alkenyl coupling monomer containing a puncture-resistant flexible silicon-oxygen chain;
[0022] Under the catalytic action of organic protonic acid, the alkenyl functional group of the alkenyl coupling monomer containing the puncture-resistant flexible silicon oxygen chain undergoes epoxidation reaction through the oxidation action of hydrogen peroxide to prepare an epoxy coupling agent containing the puncture-resistant flexible silicon oxygen chain.
[0023] Preferably, the organic protonic acid catalyst is formic acid or acetic acid.
[0024] Preferably, the preparation method of the puncture-resistant flexible silicone chain containing phenyl crosslinking agent is: through the alkenyl functional group of vinyl dimethyl ethoxy silane and the Si-H functional group of 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane to produce an addition reaction, and the amount of vinyl dimethyl ethoxy silane and 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane participating in the reaction is controlled to be (2.01-2.05): 1, so as to prepare the puncture-resistant flexible silicone chain containing phenyl crosslinking agent.
[0025] Preferably, the amount of the epoxy coupling agent containing the puncture-resistant flexible silicon-oxygen chain in the separately modified epoxidized graphene nanosheets grafted with puncture-resistant flexible silicon-oxygen chains is 5-20wt% of the amount of the hydroxylated graphene nanosheets;
[0026] Preferably, the amount of the epoxy coupling agent containing the puncture-resistant flexible silicon oxygen chain in the co-modified epoxidized graphene nanosheets grafted with puncture-resistant flexible silicon oxygen chains is 3-10wt% of the amount of the hydroxylated graphene nanosheets, and the amount of the cross-linking agent containing phenyl on the puncture-resistant flexible silicon oxygen chain is 2-10wt% of the amount of the hydroxylated graphene nanosheets.
[0027] Preferably, the amount of the epoxidized graphene nanosheets grafted with puncture-resistant flexible silicon-oxygen chains in the graphene-grafted nylon resin PA-gC(n) is 5-15wt% of the amount of the nylon resin.
[0028] A preparation method of an eleven-layer co-extruded film containing PE-PA-EVOH material comprises the following steps: ingredients are prepared according to the formula of the eleven-layer co-extruded film containing PE-PA-EVOH material, raw materials of each film layer are respectively put into the hoppers of eleven screw extruders of an eleven-layer co-extruded film blow molding unit, molten resins are converged at the die head through a diverter, extruded, blown, and pulled through a die head, cooled, and rolled up, so as to prepare the eleven-layer co-extruded film containing PE-PA-EVOH material.
[0029] Beneficial effects: Epoxy graphene grafted with puncture-resistant flexible silicon oxygen chains is obtained by functionally modifying graphene with extremely high strength and hardness using an epoxy coupling agent containing a puncture-resistant flexible silicon oxygen chain alone or using an epoxy coupling agent containing a puncture-resistant flexible silicon oxygen chain and a cross-linking agent containing phenyl groups on the puncture-resistant flexible silicon oxygen chain together;
[0030] The terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin undergoes a ring-opening reaction with the epoxy functional group of the epoxy graphene grafted with a puncture-resistant flexible silicon-oxygen chain, thereby preparing a graphene-grafted nylon resin PA-gC(n) with excellent mechanical properties;
[0031] The polyethylene resin PE was functionally modified by using graphene-grafted nylon resin PA-gC(n) and ethylene-vinyl alcohol copolymer resin EVOH with excellent barrier properties, and an eleven-layer co-extrusion film containing PE-PA-EVOH material with excellent strength properties was prepared by using an eleven-layer co-extrusion blow molding film-forming process.
[0032] The experimental results show that the tensile strength of the eleven-layer co-extruded film containing PE-PA-EVOH material prepared by the present invention reaches more than 40MPa, the elongation at break reaches more than 550%, and the total puncture resistance reaches more than 130N, which meets the technical requirements of the inner bag tensile strength ≥28.0MPa, elongation at break ≥550%, and total puncture resistance ≥120N of the inner bag material of the multilayer liquid bag specified in the TB / T2689.4-2018 "Railway Freight Containerization Transport Part 4: Disposable Container Liquid Container Bags" standard;
[0033] The invention provides an eleven-layer co-extruded film product containing PE-PA-EVOH material, which has excellent mechanical strength and puncture resistance and can be used as an inner layer material of a disposable multi-layer container liquid bag. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the product structure diagram of the eleven-layer co-extruded film containing PE-PA-EVOH material;
[0035] Among them, 1a-LLDPE layer, 1b-LLDPE / EVA layer, 2a-first UHMWPE layer, 2b-second UHMWPE layer, 3a-first PE-g-MAH layer, 3b-second PE-g-MAH layer, 4a-first PA-gC(n) layer, 4b-second PA-gC(n) layer, 5a-third PE-g-MAH layer, 5b-fourth PE-g-MAH layer, 6-EVOH layer. DETAILED DESCRIPTION
[0036] Experimental Example 1:
[0037] The epoxy coupling agent containing a puncture-resistant flexible silicone chain is prepared, and the preparation steps are as follows:
[0038] Step 1: The alkenyl functional group of 1,7-divinyl-octamethyltetrasiloxane reacts with the Si-H functional group of dimethylethoxysilane by addition reaction, and the molar ratio of 1,7-divinyl-octamethyltetrasiloxane to dimethylethoxysilane is controlled to be 1.02:1, to generate an alkenyl coupling monomer containing a puncture-resistant flexible silicon-oxygen chain, and its chemical structure is:
[0039] ;
[0040] Step 2: Using hydrogen peroxide as an oxidant, an organic protonic acid catalyst is used to catalyze the epoxidation reaction of the olefinic functional group of the olefinic coupling monomer containing a puncture-resistant flexible silicon oxygen chain to generate an epoxy coupling agent containing a puncture-resistant flexible silicon oxygen chain, and its chemical structure is:
[0041] ;
[0042] Among them, the organic protonic acid catalyst is selected to use formic acid or acetic acid; formic acid is preferably used in this experimental example;
[0043] The specific experimental steps for preparing the epoxy coupling agent containing the puncture-resistant flexible silicone chain are as follows:
[0044] Preparation of an olefin coupling monomer containing a puncture-resistant flexible siloxane chain: under the protection of nitrogen, 3.4 g of 1,7-divinyl-octamethyltetrasiloxane and 30 mL of anhydrous tetrahydrofuran were added to a three-necked flask, and stirred at room temperature until all dissolved, and then 10 mL of anhydrous tetrahydrofuran solution containing 1.0 g of dimethylethoxysilane and 5 drops of Custer catalyst were added dropwise to the three-necked flask, the temperature was raised to 70° C., stirred and refluxed for 10 h, cooled to room temperature, the solvent was removed by rotary evaporation, and vacuum dried to obtain an olefin coupling monomer containing a puncture-resistant flexible siloxane chain;
[0045] The nuclear magnetic resonance hydrogen spectrum of the olefin coupling monomer containing the puncture-resistant flexible silicon oxygen chain is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.02(s, 6H), 0.05(s, 6H), 0.09(s, 6H), 0.13(s, 6H), 0.20(s, 6H), 0.77-0.82(m, 4H), 1.10-1.14(t, 3H), 3.65-3.71(m, 2H), 5.72-5.82(dd, 2H), 6.02-6.09(t, 1H);
[0046] Preparation of an epoxy coupling agent containing a puncture-resistant flexible siloxane chain: adding 1.5 g of an olefin coupling monomer containing a puncture-resistant flexible siloxane chain and 3 mL of formic acid into a three-necked flask, heating to 40° C. and stirring for 15 min, adding 7.5 mL of 30 wt% hydrogen peroxide dropwise into the three-necked flask within 1 h, heating to 60° C. and stirring for 6 h, washing with deionized water until neutral, rotary evaporation to remove the solvent, and vacuum drying to obtain an epoxy coupling agent containing a puncture-resistant flexible siloxane chain;
[0047] The nuclear magnetic resonance hydrogen spectrum of the epoxy coupling agent containing the puncture-resistant flexible silicon oxygen chain is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.02(s, 6H), 0.04(s, 6H), 0.10(s, 6H), 0.13(s, 6H), 0.19(s, 6H), 0.77-0.83(m , 4H), 1.10-1.14(t, 3H), 2.37-2.42(m, 1H), 3.46-3.47(d, 2H), 3.65-3.71(m, 2H).
[0048] Experimental Example 2:
[0049] Preparation of a puncture-resistant flexible siloxane chain containing phenyl crosslinker: The alkenyl functional group of vinyl dimethyl ethoxy silane is reacted with the Si-H functional group of 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane by addition reaction, and the molar ratio of vinyl dimethyl ethoxy silane to 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane is controlled to be 2.03:1, to generate a puncture-resistant flexible siloxane chain containing phenyl crosslinker, the chemical structure of which is:
[0050] ;
[0051] The specific experimental steps for preparing a cross-linking agent containing phenyl groups on a puncture-resistant flexible silicon-oxygen chain are as follows: under the protection of nitrogen, 2.7 g of 3-phenyl-1,1,3,5,5-pentamethyltrisiloxane and 30 mL of anhydrous tetrahydrofuran are added to a three-necked flask, stirred at room temperature until completely dissolved, and then 20 mL of anhydrous tetrahydrofuran solution containing 2.6 g of vinyldimethylethoxysilane and 5 drops of Custer catalyst are added dropwise to the three-necked flask, the temperature is raised to 70° C., stirred and refluxed for 10 h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain a cross-linking agent containing phenyl groups on a puncture-resistant flexible silicon-oxygen chain;
[0052] The nuclear magnetic resonance hydrogen spectrum of the cross-linking agent containing phenyl on the puncture-resistant flexible silicon oxygen chain is characterized as follows: 1H NMR (CDCl3, 400MHz) δ: 0.03 (s, 12H), 0.11 (s, 12H), 0.76-0.84 (m, 8H), 1.09-1.13 (t, 6H), 1.22 (s, 3H), 3.65-3.71 (m, 4H), 7.27-7.51 (m, 5H).
[0053] Experimental Example 3:
[0054] Preparation of graphene grafted nylon resin PA-gC(n)-Ⅰ: functional modification of hydroxylated graphene with an epoxy coupling agent containing a puncture-resistant flexible siloxane chain is performed to obtain epoxidized graphene I grafted with a puncture-resistant flexible siloxane chain, and ring-opening reaction is performed between epoxidized graphene I and the terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin to prepare graphene grafted nylon resin PA-gC(n)-Ⅰ; wherein C(n) is the chemical molecular formula of graphene;
[0055] The experimental steps for preparing graphene-grafted nylon resin PA-gC(n)-Ⅰ are as follows:
[0056] 5 g of hydroxylated graphene (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a thickness of 5-10 nm and a sheet diameter of 3-8 μm), 20 mL of deionized water and 80 mL of anhydrous tetrahydrofuran were added to a three-necked flask, stirred and dissolved at room temperature for 30 min, and ultrasonically dispersed for 30 min. Then, 20 mL of anhydrous tetrahydrofuran solution containing 0.6 g of an epoxy coupling agent containing a puncture-resistant flexible silicon oxygen chain was added dropwise to the three-necked flask. After the addition was completed, 1 mL of ammonia water was added, the temperature was raised to 40°C, stirred and reacted for 6 h, and the graphene was repeatedly washed and filtered with anhydrous tetrahydrofuran and anhydrous ethanol in turn, and vacuum dried at 60°C for 10 h to obtain epoxy graphene I grafted with a puncture-resistant flexible silicon oxygen chain;
[0057] 8 g of nylon resin (purchased from Zhuzhou Times New Materials Technology Co., Ltd., brand XCGA035), 20 mL of anhydrous tetrahydrofuran and 80 mL of anhydrous N,N-dimethylformamide were added to a three-necked flask, the temperature was raised to 60°C and stirred until completely dissolved. Under nitrogen protection, 10 mL of anhydrous tetrahydrofuran solution containing 0.8 g of epoxidized graphene I grafted with puncture-resistant flexible silicon oxygen chains was slowly added to the three-necked flask, the temperature was raised to 80°C and stirred for reaction for 6 h, the mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and the mixture was vacuum dried at 120°C for 8 h to obtain graphene grafted nylon resin PA-gC(n)-Ⅰ.
[0058] Experimental Example 4:
[0059] Preparation of graphene grafted nylon resin PA-gC(n)-Ⅱ: Hydroxylated graphene is functionally modified with an epoxy coupling agent containing a puncture-resistant flexible siloxane chain and a cross-linking agent containing phenyl groups on the puncture-resistant flexible siloxane chain to obtain epoxidized graphene II grafted with a puncture-resistant flexible siloxane chain. Epoxidized graphene II undergoes a ring-opening reaction with the terminal amino functional group or the terminal carboxyl functional group on the main chain of the molecule in the nylon resin to prepare graphene grafted nylon resin PA-gC(n)-Ⅱ. The specific experimental steps refer to the preparation experiment of graphene grafted nylon resin PA-gC(n)-Ⅰ, and the only difference is that 0.3 g of epoxy coupling agent containing a puncture-resistant flexible siloxane chain and 0.3 g of cross-linking agent containing phenyl groups on the puncture-resistant flexible siloxane chain are used to replace 0.6 g of epoxy coupling agent containing a puncture-resistant flexible siloxane chain. Embodiment 1:
[0060] like Figure 1 As shown, the product structure of an eleven-layer co-extruded film I containing PE-PA-EVOH material is:
[0061] LLDPE layer 1a, the formula of this layer is 100wt% linear low-density polyethylene resin LLDPE (purchased from Yuyao Hongyang Plastic Chemical Co., Ltd., brand 2045G), the amount of this layer is 15 parts by weight;
[0062] The first UHMWPE layer 2a, the formula of this layer is 100wt% ultra-high molecular weight polyethylene resin UHMWPE (purchased from Dongguan Xinshengli Plastic New Material Technology Co., Ltd., brand L4000), the amount of this layer is 10 parts by weight;
[0063] The first PE-g-MAH layer 3a, the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH (purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., brand 4288), the amount of this layer is 2.5 parts by weight;
[0064] The first PA-gC(n) layer 4a, the formula of this layer is 100wt% graphene grafted nylon resin PA-gC(n)-Ⅰ, and the amount of this layer is 15 parts by weight;
[0065] The third PE-g-MAH layer 5a, the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, and the amount of this layer is 2.5 parts by weight;
[0066] EVOH layer 6, the formula of this layer is 100wt% ethylene-vinyl alcohol copolymer resin EVOH (purchased from Guangzhou Best New Material Technology Co., Ltd., brand ET3803RB), the amount of this layer is 10 parts by weight;
[0067] The fourth PE-g-MAH layer 5b, the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, and the amount of this layer is 2.5 parts by weight;
[0068] The second PA-gC(n) layer 4b, the formula of this layer is 100wt% graphene grafted nylon resin PA-gC(n)-Ⅰ, and the amount of this layer is 15 parts by weight;
[0069] The second PE-g-MAH layer 3b, the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, and the amount of this layer is 2.5 parts by weight;
[0070] The second UHMWPE layer 2b, the formula of this layer is 100wt% ultra-high molecular weight polyethylene resin UHMWPE, and the amount of this layer is 10 parts by weight;
[0071] LLDPE / EVA layer 1b, the formula of this layer is 70wt% linear low-density polyethylene resin LLDPE and 30wt% ethylene-vinyl acetate copolymer EVA (purchased from Suzhou Tingchang Plastic Chemical Co., Ltd., brand 265), and the amount of this layer is 15 parts by weight. Embodiment 2:
[0072] A method for preparing an eleven-layer co-extruded film I containing PE-PA-EVOH material, specifically comprising: respectively feeding the raw materials of each film layer into the hoppers of eleven screw extruders of an eleven-layer co-extruded film blow molding unit, the molten resins are combined at the die head through a diverter, extruded through a die head, blown and pulled (the blow ratio is controlled at 2.8), cooled, and rolled up to prepare an eleven-layer co-extruded film I containing PE-PA-EVOH material with a thickness of about 125 μm;
[0073] Among them, the process parameters of the screw extruder corresponding to the EVOH layer are set as follows: the temperatures of zones 1-3 are 180°C, 200°C, and 210°C, respectively, the flow channel temperature is 205°C, and the rotation speed is 40r / min;
[0074] The process parameters of the screw extruder corresponding to the PE-g-MAH layer were set as follows: the temperatures of zones 1-3 were 115 °C, 145 °C, and 160 °C, respectively, the flow channel temperature was 150 °C, and the rotation speed was 15 r / min;
[0075] The process parameters of the screw extruder corresponding to the PA-gC(n) layer were set as follows: the temperatures of zones 1-3 were 200°C, 230°C, and 270°C, respectively, the flow channel temperature was 265°C, and the rotation speed was 60 r / min;
[0076] The process parameters of the screw extruder corresponding to the UHMWPE layer were set as follows: the temperatures of zones 1-3 were 130°C, 160°C, and 190°C, respectively, the flow channel temperature was 185°C, and the rotation speed was 30 r / min;
[0077] The process parameters of the screw extruder corresponding to the LLDPE layer were set as follows: the temperatures of zones 1-3 were 120°C, 150°C, and 170°C, respectively, the flow channel temperature was 165°C, and the rotation speed was 30 r / min;
[0078] The process parameters of the screw extruder corresponding to the LLDPE / EVA layer were set as follows: the temperatures of zones 1-3 were 120°C, 150°C, and 170°C, respectively, the flow channel temperature was 165°C, and the rotation speed was 30 r / min. Embodiment three:
[0079] An eleven-layer co-extruded film II containing PE-PA-EVOH material, wherein the formula and dosage of each film layer in the product structure are different from those of the eleven-layer co-extruded film I containing PE-PA-EVOH material in Example 1 only in that: the graphene-grafted nylon resin PA-gC(n)-II is used to replace the graphene-grafted nylon resin PA-gC(n)-I in the first PA-gC(n) layer 4a and the second PA-gC(n) layer 4b;
[0080] The preparation method of an eleven-layer co-extruded film II containing PE-PA-EVOH material is the same as the preparation method of the eleven-layer co-extruded film I containing PE-PA-EVOH material in Example 2.
[0081] Comparative Example:
[0082] Preparation of eleven-layer co-extruded film containing PE-PA-EVOH material: Compared with the eleven-layer co-extruded film I containing PE-PA-EVOH material, the only difference is that the graphene grafted nylon resin PA-gC(n)-I is replaced by linear low-density polyethylene resin LLDPE.
[0083] Performance Test:
[0084] According to the test method for multi-layer liquid bag inner bag materials specified in the TB / T 2689.4-2018 "Railway Freight Containerization Transport Part 4: Disposable Container Liquid Container Bags", the performance of the eleven-layer co-extruded film containing PE-PA-EVOH material was tested, and the test results are shown in Table 1-2 below;
[0085] Table 1 Experimental results of mechanical properties of 11-layer co-extruded films containing PE-PA-EVOH
[0086]
[0087] Note: Test method for mechanical properties: Use Instron 5565 universal tensile testing machine to measure the longitudinal tensile strength of the product in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; the test speed is 5mm / min;
[0088] Table 2 Puncture performance test results of 11-layer co-extruded film containing PE-PA-EVOH material
[0089]
[0090] Note: The total puncture resistance test of the inner bag is carried out according to the test method specified in Appendix C of GB / T 17643-2011;
[0091] Through comprehensive analysis of the above experimental results, the following conclusions can be drawn:
[0092] The eleven-layer co-extruded film containing PE-PA-EVOH material modified by graphene-grafted nylon resin PA-gC(n) has achieved significant technical improvements in mechanical properties and puncture resistance.
[0093] Among them, the phenyl functional groups contained in the puncture-resistant flexible silicon oxygen chain in the graphene-grafted nylon resin PA-gC(n) have a better effect on improving the mechanical properties and puncture resistance of the eleven-layer co-extruded film containing PE-PA-EVOH material.
Claims
1. An eleven-layer co-extruded film containing PE-PA-EVOH material, characterized in that: The product structure of the eleven-layer co-extruded film is the following layers arranged in sequence: LLDPE layer (1a), the formula of this layer is 100wt% linear low-density polyethylene resin LLDPE, and the amount of this layer is 10-20 parts by weight; A first UHMWPE layer (2a), the formula of which is 100 wt% ultra-high molecular weight polyethylene resin UHMWPE, and the amount of which is 5-15 parts by weight; The first PE-g-MAH layer (3a), the formula of this layer is 100wt% maleic anhydride grafted polyethylene resin PE-g-MAH, and the amount of this layer is 1-5 parts by weight; The first PA-gC(n) layer (4a) has a formula of 100 wt% graphene-grafted nylon resin PA-gC(n) and an amount of 10-20 parts by weight; A third PE-g-MAH layer (5a), the formulation and dosage of which are the same as those of the first PE-g-MAH layer (3a); EVOH layer (6), the formula of this layer is 100wt% ethylene-vinyl alcohol copolymer resin EVOH, and the amount of this layer is 5-15 parts by weight; A fourth PE-g-MAH layer (5b), the formulation and dosage of which are the same as those of the first PE-g-MAH layer (3a); A second PA-gC(n) layer (4b), the formulation and dosage of which are the same as those of the first PA-gC(n) layer (4a); A second PE-g-MAH layer (3b), the formulation and dosage of which are the same as those of the first PE-g-MAH layer (3a); The second UHMWPE layer (2b) has the same formulation and dosage as the first UHMWPE layer (2a) LLDPE / EVA layer (1b), the formula of this layer is 60-90wt% linear low-density polyethylene resin LLDPE and 10-40wt% ethylene-vinyl acetate copolymer EVA, and the amount of this layer is 10-20 parts by weight; The preparation method of graphene grafted nylon resin PA-gC(n) is as follows: The epoxy coupling agent containing puncture-resistant flexible silicon oxygen chain alone or the epoxy coupling agent containing puncture-resistant flexible silicon oxygen chain and the cross-linking agent containing phenyl on the puncture-resistant flexible silicon oxygen chain are used to functionally modify the hydroxylated graphene nanosheets to obtain epoxy graphene nanosheets grafted with puncture-resistant flexible silicon oxygen chain; The graphene grafted nylon resin PA-gC(n) is prepared by a ring-opening reaction between the terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin and the epoxy functional group of the epoxidized graphene nanosheet grafted with a puncture-resistant flexible silicon oxygen chain.
2. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 1, characterized in that: The chemical structural formula of the epoxy coupling agent containing the puncture-resistant flexible silicone chain is: 。 3. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 2, characterized in that: The preparation method of the epoxy coupling agent containing the puncture-resistant flexible silicone chain is as follows: The alkenyl functional group of 1,7-divinyl-octamethyltetrasiloxane and the Si-H functional group of dimethylethoxysilane undergo an addition reaction, and the molar ratio of 1,7-divinyl-octamethyltetrasiloxane and dimethylethoxysilane participating in the reaction is controlled to be (1.01-1.05):1, thereby generating an alkenyl coupling monomer containing a puncture-resistant flexible silicon-oxygen chain; Under the catalytic action of organic protonic acid, the alkenyl functional group of the alkenyl coupling monomer containing the puncture-resistant flexible silicon oxygen chain undergoes epoxidation reaction through the oxidation action of hydrogen peroxide to prepare an epoxy coupling agent containing the puncture-resistant flexible silicon oxygen chain.
4. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 3, characterized in that: The organic protonic acid catalyst is formic acid or acetic acid.
5. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 1, characterized in that: The chemical structural formula of the cross-linking agent containing phenyl groups on the puncture-resistant flexible silicone chain is: 。 6. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 5, characterized in that: The preparation method of the cross-linking agent containing phenyl groups on the puncture-resistant flexible silicon-oxygen chain comprises: an addition reaction is carried out between the alkenyl functional group of vinyl dimethyl ethoxy silane and the Si-H functional group of 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane, and the molar ratio of the vinyl dimethyl ethoxy silane and the 3-phenyl-1,1,3,5,5-pentamethyl trisiloxane participating in the reaction is controlled to be (2.01-2.05):1, so as to prepare the cross-linking agent containing phenyl groups on the puncture-resistant flexible silicon-oxygen chain.
7. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 1, characterized in that: The amount of the epoxy coupling agent containing the puncture-resistant flexible silicon-oxygen chain in the separately modified epoxidized graphene nanosheet grafted with the puncture-resistant flexible silicon-oxygen chain is 5-20wt% of the amount of the hydroxylated graphene nanosheet; The amount of the epoxy coupling agent containing the puncture-resistant flexible silicon oxygen chain in the co-modified epoxidized graphene nanosheets grafted with puncture-resistant flexible silicon oxygen chain is 3-10wt% of the amount of the hydroxylated graphene nanosheets, and the amount of the cross-linking agent containing phenyl on the puncture-resistant flexible silicon oxygen chain is 2-10wt% of the amount of the hydroxylated graphene nanosheets.
8. The eleven-layer co-extruded film containing PE-PA-EVOH material according to claim 1, characterized in that: The amount of the epoxy graphene nanosheets grafted with puncture-resistant flexible silicon-oxygen chains in the graphene-grafted nylon resin PA-gC(n) is 5-15wt% of the amount of the nylon resin.
9. The method for preparing an eleven-layer co-extruded film containing PE-PA-EVOH material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: mixing ingredients according to the formula of an eleven-layer co-extruded film containing PE-PA-EVOH material, respectively feeding the raw materials of each film layer into the hoppers of eleven screw extruders of an eleven-layer co-extruded film blow molding unit, combining the molten resin at the die head through a diverter, extruding, inflating, pulling, cooling, and winding, so as to prepare the eleven-layer co-extruded film containing PE-PA-EVOH material.
10. The use of an eleven-layer co-extruded film containing PE-PA-EVOH material according to any one of claims 1 to 8, characterized in that: The eleven-layer co-extruded film containing PE-PA-EVOH material is used as the inner layer material of the disposable multi-layer container liquid bag.
